2011
DOI: 10.1111/j.1748-7692.2010.00457.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in spatial and temporal distribution and vocal behavior of Blainville's beaked whales (Mesoplodon densirostris) during multiship exercises with mid‐frequency sonar

Abstract: The number and distribution of vocalizing groups of Blainville's beaked whales (Mesoplodon densirostris) were analyzed before, during, and after multiship mid‐frequency active sonar operations at the US Navy's Atlantic Undersea Test and Evaluation Center (AUTEC) in the Bahamas. Groups of foraging animals were isolated by detecting their echolocation clicks using an array of bottom‐mounted hydrophones. Two data sets were evaluated consisting of 115 and 240 h of acoustic data in May 2007 and 2008, respectively. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
100
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(105 citation statements)
references
References 23 publications
4
100
0
Order By: Relevance
“…Detailed habitat usage by beaked whales within TOTO has been historically monitored using combinations of cabled hydrophones and visual observations. These observations have identified significant and persistent spatial variability in preferred foraging habitat within TOTO (Moretti et al 2006, McCarthy et al 2011, Claridge 2013. DSL characteristics in these areas of TOTO were compared with the waters off Abaco Island, a nearby region where the Blainville's beaked whales exhibit higher reproduction rates relative to their populations in TOTO (Claridge 2013).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Detailed habitat usage by beaked whales within TOTO has been historically monitored using combinations of cabled hydrophones and visual observations. These observations have identified significant and persistent spatial variability in preferred foraging habitat within TOTO (Moretti et al 2006, McCarthy et al 2011, Claridge 2013. DSL characteristics in these areas of TOTO were compared with the waters off Abaco Island, a nearby region where the Blainville's beaked whales exhibit higher reproduction rates relative to their populations in TOTO (Claridge 2013).…”
Section: Introductionmentioning
confidence: 92%
“…It is bounded on 2 sides by very shallow waters, while the maximum depths exceed 2000 m. In TOTO, beaked whales are repeatedly exposed to high levels of military activities, including sonar, which have been shown to result in rare mass strandings and likely more frequent population level reductions in fitness (Fernández et al 2005, Cox et al 2006, Claridge 2013. Field sampling was conducted in 4 zones within TOTO based on the long-term observations of foraging behavior of Blainville's beaked whales using the Atlantic Undersea Test and Evaluation Center (AUTEC) hydrophone recordings and visual surveys (McCarthy et al 2011, Tyack et al 2011, Claridge 2013: the West zone as a frequently used habitat, the East zone as a less-commonly used habitat within the AUTEC range, and the North and South zones as immediately adjacent areas to the AUTEC range and likely used as refuge during the navy sonar exercises (Tyack et al 2011). Data from these sampling zones were compared with the region approximately 144 km to the north of the range, southwest of the island of Abaco, which has been identified as a less disturbed area for beaked whale populations with a greater abundance of juveniles compared to the populations in TOTO (Claridge 2013).…”
Section: Study Site and Survey Designmentioning
confidence: 99%
See 2 more Smart Citations
“…Tyack et al (2011) found that one animal stopped feeding above 138 SPL dB (or a cumulative sound exposure level (SEL) of 142 dB re 1 µPa 2 -s), while a second experiencing a received level of 146 re 1 µPa swam 10s of km away (an average of 54 ± 10 km) from the center of the testing range and remained out of the area for 2-3 days (McCarthy et al, 2011;Tyack et al, 2011). The calls of beaked whales in the area also decreased during sonar exposure and did not recover to pre-exposure levels for up to 108 h after exposure, although calls were produced even at estimated exposure levels of 157 dB re 1 µPa (rms) (McCarthy et al, 2011).…”
Section: The Received Levels Of Sonar and Beaked Whales Impactsmentioning
confidence: 99%